Experimental and numerical study on seismic performance of Q690 high-strength steel plate reinforced joints. (April 2021) - Guo, Hongchao; Zhou, Xizhe; Li, Wei; Liu, Yunhe; Yang, Dixiong
Abstract: The steel structure joints in the seismic fortification areas should have good rotation capacity while having sufficient bearing capacity. The plate reinforced joint can not only improve the bending bearing capacity of the beam end, but also effectively ensure that the beam-end welds does not undergo brittle failure and improve the ductility of the joint. A low-cyclic loading test of 6 Q690 high-strength steel plate reinforced joints was carried out in this paper, revealing the failure mechanism and energy dissipation mechanism of the joints, the influence laws of different reinforcement forms, steel strength grades, joint region reinforcement measures and key control parameters on the joints seismic performances were discussed. The results indicated that Due to the direct welding between the cover plate and the beam flange and the cylinder, the connection stiffness of the "cover plate reinforced" joint is large, and the rotational restraint force on the joint is strong, so the deformation capacity of the joint is weaker than the "flange plate transition" joint, The use of ordinary steel for steel beams will reduce the bearing capacity of the joints, but it can achieve higher ductility and energy dissipation capacity. when the joint region welding steel plate is reinforced, the ultimate bearing capacity of the joints was elevated by 14.14% and 13.74% respectively, while the ductility coefficient was reduced by 14.09% and 31.42%, which limits the rotation capacity of the joints. For flange plate transition joints, it is suggested that the length of the flange plate should be (0.6–0.85) hb and the thickness should be (1.2–1.4) tb . For cover plate reinforced joints, it is suggested that the length of the cover plate should be (0.6–0.85) hb and the thickness should be (0.7–1.1) tb . The study provides a theoretical basis for the engineering application and promotion of high-strength steel joints in seismic fortification areas. Highlights: A low-cyclic loading tests of 6 Q690 high-strength steel plate reinforced joints. Consider the different reinforcement forms, steel strength grades and the joint region reinforcement measures in the tests. Through local plate type reinforcement, the seismic behavior of connections could be improved significantly. The failure modes, the seismic behaviors and the mechanical indexes of the specimens were reported. The parameter analysis is carried out for flange Plate and cover plate of high-strength steel plate reinforced joints.